2019
DOI: 10.1002/14651858.cd002243.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids for treating sepsis in children and adults

Abstract: Analysis 2.5. Comparison 2 Continuous infusion versus bolus administration of corticosteroids, Outcome 5 Hospital mortality.... Analysis 2.6. Comparison 2 Continuous infusion versus bolus administration of corticosteroids, Outcome

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
104
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 94 publications
(109 citation statements)
references
References 157 publications
3
104
1
1
Order By: Relevance
“…Corticosteroids is commonly used for treating sepsis [20,21]. The results of previous studies showed a mild increase in sodium level and increased the risk of hypernatremia with high-certainty evidence [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corticosteroids is commonly used for treating sepsis [20,21]. The results of previous studies showed a mild increase in sodium level and increased the risk of hypernatremia with high-certainty evidence [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroids is commonly used for treating sepsis [20,21]. The results of previous studies showed a mild increase in sodium level and increased the risk of hypernatremia with high-certainty evidence [20][21][22][23]. It is suggested that administration of corticosteroids is associated with reduced 28day mortality compared with placebo use or standard supportive care [22].…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroids produced by adrenocortical cells and their synthetic analogues have multiple biological effects, including immune modulation (78,79). Several clinical trials conducted over the years provided discordant results (80)(81)(82)(83). Among them, ADRENAL stands as one of the largest RCTs (n = 3800), which showed that hydrocortisone did not decrease mortality in septic shock patients who needed mechanical ventilation (83).…”
Section: Painful and Inspiring Lessons From Sepsis For Covid-19 Immunmentioning
confidence: 99%
“…Among them, ADRENAL stands as one of the largest RCTs (n = 3800), which showed that hydrocortisone did not decrease mortality in septic shock patients who needed mechanical ventilation (83). Nevertheless, a very (80). There is also some renewed interest in the combination of hydrocortisone, ascorbic acid, and thiamine for the treatment of sepsis, with the establishment of several RCTs, such as the ACTS trial (NCT03389555) (84).…”
Section: Painful and Inspiring Lessons From Sepsis For Covid-19 Immunmentioning
confidence: 99%
“…The discipline of paediatric neurology encompasses diseases and disorders of the brain, spinal cord, peripheral nervous system, autonomic system, muscle and blood vessels that effects individual in this age group. Over the past two decades, high-dose of corticosteroids therapy (an approach already used to treat several neurological syndromes such as multiple sclerosis) has been used in various studies in the eld of epilepsy in order to avoid the development of adverse effects and maintained long term e cacy [1][2][3][4]. In the USA in 2019, corticosteroids were the most common speci c cause for drug-related adverse effects, accounting for 10.3% of all drug related adverse effects and 141,000 hospital stays [5].…”
Section: Introductionmentioning
confidence: 99%